Peri-prostatovesicular smooth muscle tumors of undetermined malignant potential: a case report. Issue 2 (May 2019) - Masciovecchio, Stefano; Di Pasquale, Alfonso B.; Ranieri, Guido; Romano, Gianfranco; Colozzi, Sara; Cipolloni, Gianluca; Coletti, Gino; Calvisi, Giuseppe; Di Clemente, Luigi
Introduction: Smooth muscle tumors of undetermined malignant potential (STUMPs) are atypical smooth muscle tumors, most of which derived from uterine tissue. STUMPs of male genitourinary system and of the male pelvic organs are uncommon. Case description: In this report, we describe the first case of peri-prostatovesicular STUMP that was treated with laparoscopic excision, in a young asymptomatic man. Conclusions: In most cases, the definitive diagnosis can be made only after surgical resection and accurate histological examination. The usefulness of adjuvant chemotherapy remains unclear, and a standardized follow-up protocol has not been described.